Evaluation of Local Government Administration and Governance in Nigeria - Anayochukwu, Grace; Ani, Vincent Anayochukwu (Local Administration Journal, 2021)
Local government (LG) is the tier of government that is closest to the people. The quest for LG administration and governance still generates exciting and healthy debate in Nigeria. This study examines the opportunities and problems, which confront the Nigerian LG system in its efforts to establish itself as a true tier of government. The main objectives of the study are to find out why, in practice, complete LG autonomy and governance is difficult in Nigeria; to investigate the level of autonomy in Nigeria’s LG system; and to suggest measures that could be adopted to reduce interference in the LG affairs in Nigeria. The theoretical framework adopted in this study is the Marxist theory. The proponents of this theory see LG as an instrument of the central government, which works as a direct means of securing proletarian compliance through suppression. A survey of 300 employees in the Nkanu West LG Area was conducted. A five-point Likert scale was used in data collection. The findings revealed that there were constitutional loopholes or contradiction that tend to provide the impetus for the unethical state government officials to nurse the inordinate desire for hedging in LG left, right, and center. This study recommends that the autonomy of LG should be based on a better income base, respect for constitutional provisions, political stability, accountability, and transparency.